Use of Social Networking Sites among Undergrade-level Women and its Effect on their Plans to Start a Business - Hossain, Tanjela; Iqbal, Md Mahbub; Shirazi, Hasan; Noor, Md. Asad (South Asian Journal of Social Sciences and Humanities, 2022)
This study looks at how Facebook, Twitter, and Instagram have impacted the business interests of Bangladeshi college-aged women. The research methodology incorporates the technology acceptance paradigm and a model of technology adoption and usage. The survey was developed, checked for accuracy, and released to the public. According to the results, students’ usage of social networking sites affects their confidence in their capacity to succeed and their desire to do so. These results have real-world and theoretical ramifications for policymakers and entrepreneurial education, such as using widely used yet cutting-edge communication and Internet tools to inspire young people to start their own businesses. In this analysis, we test the hypothesis that there is a connection between the time spent on social networking sites (SNS) and measures of confidence in, and desire for, starting one’s own business. Over two hundred and fifty female students from Private Universities in Bangladesh participated in online questionnaires and correlation tests. More time spent on social networking sites is correlated with more serious business thinking and behavior. Students of all sexes and all ages use Facebook, but younger students and women in particular associate the platform with entrepreneurial aspirations and attitudes more strongly than their male counterparts. There is a greater understanding of the relationship between social media presence and entrepreneurship factors because to this research. The researchers sorted the interviewees’ responses into four groups based on their findings: how often they used SNS, how much they felt supported by SNS, how secure they felt in their entrepreneurial conduct, and how ambitious they wanted to be as business owners’ Important motifs were also determined for each class. Institutions of higher learning may and should use social media to promote and educate aspiring business owners.